2020
DOI: 10.3171/2019.4.jns183458
|View full text |Cite
|
Sign up to set email alerts
|

Results of 1940 embolizations for dural arteriovenous fistulas: Japanese Registry of Neuroendovascular Therapy (JR-NET3)

Abstract: OBJECTIVEEmbolization is the most common treatment for dural arteriovenous fistulas (dAVFs). A retrospective, multicenter observational study was conducted in Japan to clarify the nature, frequency, and risk factors for complications of dAVF embolization.METHODSPatient data were derived from the Japanese Registry of Neuroendovascular Therapy 3 (JR-NET3). A total of 40,169 procedures were registered in JR-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…The complication- (3%) and procedure-related (0%) mortality rates in our cohort were acceptable and in line with previous studies [ 11 , 16 , 19 , 25 ]. To date, the largest case series on cranial DAVFs in the literature reported a complication rate of 7.7% and a mortality rate of 0.8% [ 11 ]. Although 2 patients were temporarily affected, no patients had permanent deficits.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The complication- (3%) and procedure-related (0%) mortality rates in our cohort were acceptable and in line with previous studies [ 11 , 16 , 19 , 25 ]. To date, the largest case series on cranial DAVFs in the literature reported a complication rate of 7.7% and a mortality rate of 0.8% [ 11 ]. Although 2 patients were temporarily affected, no patients had permanent deficits.…”
Section: Discussionsupporting
confidence: 92%
“…In general, complications occurred in patients with DAVF location in the falcotentorial group (tentorial and anterior cranial fossa). This confirms the results of a recent study by Hiramatsu et al [11] that demonstrated nonsinus-type location as a predictor of complications. Other studies also showed increased complication rates for the tentorial location in up to 31% [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of ACC dAVFe is reportedly 3.8%. 6) The ACC is located in the extracranial cavity, being anatomically associated with several venous return routes; therefore, in patients with ACC dAVF, reflux from the inferior petrosal sinus (IPS) to the cavernous sinus and emissary-vein-mediated reflux to the anterior medullary vein (AMV) has been reported. 7) In this study, we report a patient with an ACC dAVF in whom reflux to the AMV appeared through a change in venous return during follow-up.…”
Section: Introductionmentioning
confidence: 99%